Geoecological Assessment of Zarafshan National Nature Park using GIS Research - R. I., Mamajanov; N. A., Safarova; T. N, Tuygunov (American Journal of Biology and Natural Sciences, 2025)
Assessment using GIS studies showed that the specific characteristics of the groves of the Zarafshan National Nature Park are the diversity of plant and soil layers, the morphological structure of the groves, and to a certain extent the groves have a complex structure. Consequently, the grove landscapes consist of various hydrogen geocomplexes, and their differentiation is greatly influenced by the environment, the morphological structure of contrasting groves, the mechanical composition of alluvial deposits, the close location of groundwater, the degree of soil salinity, and the heterogeneity of ecological conditions even in local areas.